Application of atomic force microscopy (AFM) in ophthalmology - Milka, Michał; Mróz, Iwona; Jastrzębska, Maria; Wrzalik, Roman; Dobrowolski, Dariusz; Roszkowska, Anna; Moćko, Lucyna; Wylęgała, Edward (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Atomic force microscopy (AFM) allows to examine surface of different biological objects in the nearly physiological conditions at the nanoscale. The purpose of this work is to present the history of introduction and the potential applications of the AFM in ophthalmology research and clinical practice. In 1986 Binnig built the AFM as a next generation of the scanning tunnelling microscope (STM). The functional principle of AFM is based on the measurement of the forces between atoms on the sample surface and the probe. As a result, the three-dimensional image of the surface with the resolution on the order of nanometres can be obtained. Yamamoto used as the first the AFM on a wide scale in ophthalmology. The first investigations used the AFM method to study structure of collagen fibres of the cornea and of the sclera. Our research involves the analysis of artificial intraocular lenses (IOLs). According to earlier investigations, e.g. Lombardo et al., the AFM was used to study only native IOLs. Contrary to the earlier investigations, we focused our measurements on lenses explanted from human eyes. The surface of such lenses is exposed to the influence of the intraocular aqueous environment, and to the related impacts of biochemical processes. We hereby present the preliminary results of our work in the form of AFM images depicting IOL surface at the nanoscale. The images allowed us to observe early stages of the dye deposit formation as well as local calcinosis. We believe that AFM is a very promising tool for studying the structure of IOL surface and that further observations will make it possible to explain the pathomechanism of artificial intraocular lens opacity formation.